A Two-dimensional Transmission Counter with a Backgammon-Drift Read-Out Technique - Sutomo Budihardjo; Hajime Fujimura; Akihiro Nohtomi; Yusuke Uozumi; Masaru Matoba (BATAN, 2006)
AbstractA new type of two-dimensional position sensitive gas counter for transmission counter with a backgammon-shaped flat electrode has been developed. The two dimensional position read-out can be achieved with the combination of the backgammon-shaped flat electrode read-out. as horizontal position and the drift time measurement read-out as vertical position. The gas counter is designed as a transmission trajectory counter that can be used to determined angle of incident charged particle in the charged particle detecting system. To check the characteristics of this gas counter, test experiments are performed with a coincidence plastic scintillation counter and p - ray source of 90Sr.